EDUCATION AS A HUMAN RIGHT: THE RISE OF THE HBCUS - Holloman, Tiffany; Siler-Holloman, LaTonia (Revista de Educação do Vale do São Francisco, 2021)
Education is a fundamental right. Historically Black Colleges and Universities in the US formed from the desire of African Americans to enjoy that right. The aim of this research was to explore the development of the HBCUs and their legacy of promoting activism. In using document analysis, a clear correlation is illustrated in the human struggle to obtain inalienable rights and the inhumanity of denial of such rights. Education for those Africans Americans affliated with HBCUs was not only sought for the sake of knowledge, but to enhance and engage the wider community.